2015
DOI: 10.1177/0963662515613678
|View full text |Cite
|
Sign up to set email alerts
|

The (de)politicisation of nuclear power: The Finnish discussion after Fukushima

Abstract: When the Fukushima accident occurred in March 2011, Finland was at the height of a nuclear renaissance, with the Government's decision-in-principle in 2010 to allow construction of two new nuclear reactors. This article examines the nuclear power debate in Finland after Fukushima. We deploy the concepts of (de)politicisation and hyperpoliticisation in the analysis of articles in the country's main newspaper. Our analysis indicates that Finnish nuclear exceptionalism manifested in the safety-related depoliticis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
17
0
3
Order By: Relevance
“…In contrast, debates focusing on political decisions about nuclear energy focus on longer-term issues. Studies examining such periods found, for example, that nuclear power was framed as an instrument to combat climate change in the UK in an effort to legitimize new nuclear plants (Doyle, 2011;Teräväinen, 2011;Teräväinen, Lehtonen, & Martiskainen, 2011), or that the stability of energy supply and national energy independence were used as arguments in favor of extending the German plants' operating time (Arlt, 2013) and the building of new ones in other countries (Doyle, 2011;Teräväinen, 2011;Ylönen, Litmanen, Kojo, & Lindell, 2017). Likely, public debate in the wake of the Swiss referendum would also center on long-term issues and objectives (e.g., the reduction of the proportion of fossil-based energy use, the expansion of the use of renewable energies, and intensification of energy efficiency) anchored in the Swiss National Energy Strategy 2050; which was finally accepted by 58% of the Swiss voters in a referendum held in May 2017.…”
Section: Public Debates About Political Decisions: Shifting Away Frommentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, debates focusing on political decisions about nuclear energy focus on longer-term issues. Studies examining such periods found, for example, that nuclear power was framed as an instrument to combat climate change in the UK in an effort to legitimize new nuclear plants (Doyle, 2011;Teräväinen, 2011;Teräväinen, Lehtonen, & Martiskainen, 2011), or that the stability of energy supply and national energy independence were used as arguments in favor of extending the German plants' operating time (Arlt, 2013) and the building of new ones in other countries (Doyle, 2011;Teräväinen, 2011;Ylönen, Litmanen, Kojo, & Lindell, 2017). Likely, public debate in the wake of the Swiss referendum would also center on long-term issues and objectives (e.g., the reduction of the proportion of fossil-based energy use, the expansion of the use of renewable energies, and intensification of energy efficiency) anchored in the Swiss National Energy Strategy 2050; which was finally accepted by 58% of the Swiss voters in a referendum held in May 2017.…”
Section: Public Debates About Political Decisions: Shifting Away Frommentioning
confidence: 99%
“…Scholarship so far has largely focused on legacy news media and disregarded the growing relevance of social media in public debates concerning nuclear power. The vast majority of studies, even recent ones (e.g., Arlt & Wolling, 2016;Kepplinger & Lemke, 2016;Kristiansen, 2017;Teräväinen, 2011;Ylönen et al, 2017), examine public debates on nuclear energy by analyzing traditional news media such as television and newspapers.…”
Section: Analyzing Social Mediamentioning
confidence: 99%
“…Following Zürn (2014, p. 51) the agents of politicization can be all individuals or groups who participate in the political process. Thus, in line with this definition the process of politicization also incorporates the communicative tactic to produce doubt regarding a scientific consensus, mainly used by the weaker party in a conflict (Bolsen and Druckman 2015;Ylönen et al 2017). Based on the work of Sarewitz (2004), this can be implemented by either (1) citing experts or scientific knowledge to legitimate the opposing viewpoint, or (2) by discrediting and criticizing the scientific consensus or its representatives.…”
Section: The Skeptics' Use Of Expert Knowledgementioning
confidence: 99%
“…Yet we know that in the Finnish domestic debate, the pro-nuclear lobby framed the 2013 contract with Rosatom in terms of the decarbonization prospects of nuclear power. The Finnish actors moreover expressed an interest in security of supply by stressing how building a modern plant would reduce the need to buy electricity from Russia (Syrjämäki, Kojo, and Litmanen 2015;Ylönen et al 2015).…”
Section: Russian Nuclear Energy Diplomacy: What Do We Know?mentioning
confidence: 99%